2017
DOI: 10.1111/his.13254
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 overexpression in ampulla of Vater carcinoma and its pre‐invasive lesions

Abstract: The present results suggest a role of the PD-1/PD-L1 axis in ampullary adenocarcinomas, and therefore this may also prompt consideration of checkpoint immunotherapy as a novel promising treatment for these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
3
20
1
Order By: Relevance
“…60 However there was limited evidence of PD-L1 signaling in MMRdeficient ampullary cancers. 61,62 In the current study, our analysis of PD-L1 expression in the MMR-deficient group revealed high frequency and levels of PD-L1, specifically in tumors with medullary-type morphology. This prompted us to investigate the MMR-intact medullary carcinomas and one-half of those (n = 2 of 4) that also exhibited PD-L1 expression.…”
Section: Discussionsupporting
confidence: 49%
“…60 However there was limited evidence of PD-L1 signaling in MMRdeficient ampullary cancers. 61,62 In the current study, our analysis of PD-L1 expression in the MMR-deficient group revealed high frequency and levels of PD-L1, specifically in tumors with medullary-type morphology. This prompted us to investigate the MMR-intact medullary carcinomas and one-half of those (n = 2 of 4) that also exhibited PD-L1 expression.…”
Section: Discussionsupporting
confidence: 49%
“…The immunohistochemical analysis (IHC) was performed using a peroxidasebased detection system, as already described [16][17][18][19], using 4 μm-thick whole sections from formalin-fixed paraffin-embedded (FFPE) tissues. The following antibodies for PD-1 (source: ABCAM, clone: NAT105, incubation pH=9, dilution 1:100), PD-L1…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The Helsinki Declaration and the international and institute's ethical regulations on research on human tissues were followed. The same series was previously investigated for PD-L1 expression (10).…”
Section: Casesmentioning
confidence: 99%
“…All samples were processed using the Galileo CK3500 Arrayer (www.isenet.it), a semiautomatic and computer-assisted Tissue Macro Array (TMA) platform, as previously described (10,29). HER2 expression was evaluated with the score used for the characterization of gastric adenocarcinoma.…”
Section: Sample Preparation and Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 1 more Smart Citation